Technology A New Dimension of Life Style During Covid-19 - Shambhoo Sharan Gupta, (Indian Journal of Mass Communication and Journalism (IJMCJ), 2024)
The human being along with all living things shows movement. There are so many activities done by human being; but COVID-19 stopped their all types work. COVID-19 has stopped their all type work and force stay at home. In Such all world’s human being are doing Yoga for healthy and fit. There are human being have changed their living style during COVID-19 in the world. Another part of the world’s human being is adapting technology; which is very important practical for future as a new concept in human life. In this research article qualitative research methods and content analysis have been used to published and broadcast from websites, news channel, and reports which described on information technology, artificial intelligence, and related from human being life. During lockdown period, the finding of this research article that the technological innovation are undergoing process of online education, observation, artificial intelligence and others are changing life’s in a new dimension. This research article described how our life is becoming based on the most modern information communication technology in the Corona period. Every kind of new systems related to information communication and technology are bound to be used in our lives.